Cancer therapeutic targets - Marshall, John L. (Springer, 2017)
In the past decade, we have experienced an explosion of new information about cancer therapeutic targets. Many of the targets have been validated by the discovery and approval of new medicines which have been approved for the treatment of cancer. On the heels of these successes, innumerable new targets and new potential therapeutics are being developed by many different groups including government agencies, pharmaceutical companies, biotechnology companies, academic institutions, and individual investigators. Understanding the expanding "universe" of cancer therapies is therefore becoming impossible and no single source exists which serves as a reference for the involved parties. Further, the interested parties have vastly different areas of expertise, from focused laboratory based science, to clinical research, to corporate and regulatory oversight. The text would be updated every two years, more often depending on pace of change, interest and sales. While useful online, this reference book would likely be kept in hard copy as well.- Resumé vydavatel
Includes index.
Keywords: maligní nádorová onemocnění; vědecký výzkum; onkologie; laboratorní diagnostika; vnitřní lékařství; molekulární biologie; farmakologie; cancer; scientific research; oncology; laboratory diagnostics; internal medicine; molecular biology; pharmacology; elektronické knihy; sborníky; electronic books; papers of several authors